Electrochemical Detection of Tryptophan Metabolites via Kynurenine Pathway by Using Nanocarbon Films. Issue 4 (30th June 2021) - Kato, Dai; Kamata, Tomoyuki; Sumimoto, Michinori
Abstract: We studied nanocarbon film electrodes with the aim of detecting tryptophan metabolites via the kynurenine pathway. The nanocarbon films were formed by using unbalanced magnetron sputtering, and they exhibited superior electrode properties including a wide potential window and a low background current as a result of the sp 3 ‐containing structure and ultraflat surface. These properties allowed us to detect certain tryptophan metabolites such as kynurenic acid (KYNA), which has a relatively high oxidation potential. We also investigated the effect of the sp 2 /sp 3 ratio of the nanocarbon film as regards the electrode activity in relation to target molecules. We found that the sp 2 /sp 3 ratio played important roles in both widening the potential window and obtaining superior electrode performance for the metabolites. The nanocarbon film with a high sp 3 content was beneficial as regards the electrode performance with respect to the detection limit and sensitivity. Compared with conventional carbon‐based electrodes, the nanocarbon film electrode with a high sp 3 content exhibited higher electrode activity against KYNA while maintaining a low background current. Computational experiments revealed that the theoretical oxidation potential ( E ox ) value for some targets coincided with that obtained in electrochemical experiments using our nanocarbon film electrode. Abstract :